Mitsuokella jalaludinii supplementation improved nutrient utilization of broilers fed low available phosphorous diet - Tang, Hooi Chia; Sieo, Chin Chin; Abdullah, Norhani; Chong, Chun Wie; Omar, Abdul Rahman; Mohamad, Rosfarizan; Ho, Yin Wan (Faculty of Animal Husbandry, Brawijaya University, 2017)
Phytase is frequently used as a feed supplement to improve availability of P in poultry. Mitsuokella jalaludinii, isolated from the rumen of cattle showed high phytase activity capable of hydrolysing phytate compounds. In this study, the efficacy of freeze-dried M. jalaludinii phytase was evaluated as a feed supplement for broilers fed low-available P (aP) diet. The results showed that freeze-dried M. jalaludinii cells with functional phytase activity significantly enhanced (p<0.05) growth performance and feed conversion ratio of broilers fed low-aP diet and the apparent digestibility of dry matter and crude protein of the feed. Phytase supplementation also enhanced retention of P, Ca, Mn, Cu, and Zn as well as the Ca and Mn content in tibia of broilers. The Ca, Mn and Zn concentrations in plasma of broilers fed low-aP diet were not significantly different than those fed normal diet, but the levels of P and Cu were significantly lower (p<0.05) than the control.